A validated tool to predict colorectal neoplasia and inform screening choice for asymptomatic subjects. Issue 7 (17th September 2013) - Wong, Martin C S; Lam, Thomas Y T; Tsoi, Kelvin K F; Hirai, Hoyee W; Chan, Victor C W; Ching, Jessica Y L; Chan, Francis K L; Sung, Joseph J Y
Abstract : Objective: We aim to develop and validate a clinical scoring system to predict the risks of colorectal neoplasia to better inform screening participants and facilitate their screening test choice. Design: We recruited 5220 Chinese asymptomatic screening participants who underwent colonoscopy in Hong Kong during 2008–2012. From random sampling of 2000 participants, independent risk factors were evaluated for colorectal neoplasia, defined as adenoma, advanced neoplasia, colorectal cancer or any combination thereof using binary regression analysis. The ORs for significant risk factors were used to develop a scoring system ranging from 0 to 6: 0–2 'average risk' (AR) and 3–6 'high risk' (HR). The other 3220 screening participants prospectively enrolled between 2008 and 2012 for screening colonoscopy formed an independent validation cohort. The performance of the scoring system for predicting colorectal neoplasia was evaluated. Results: The prevalence of colorectal neoplasia in the derivation and validation cohorts was 31.4% and 30.8%, respectively. Using the scoring system developed, 78.9% and 21.1% in the validation cohort were classified as AR and HR, respectively. The prevalence of colorectal neoplasia in the AR and HR groups was 27.1% and 44.6%, respectively. The subjects in the HR group had 1.65-fold (95% CI 1.49 to 1.83) increased prevalence of colorectal neoplasia than the AR group. Conclusions: The scoring system based on age, gender, smoking, family history, Body Mass Index and self-reported diabetes is useful in predicting the risk of colorectal neoplasia.